Bioinformatics analysis of microarray profiling identifies the mechanism of focal adhesion kinase signalling pathway in proliferation and apoptosis of breast cancer cells modulated by green tea polyphenol epigallocatechin 3-gallate. (5th September 2018) - Luo, Xiao; Guo, Lihua; Zhang, Lirong; Hu, Yu; Shang, Dongmei; Ji, Degang
Abstract: Objectives: This study aimed to investigate potential gene and signal pathway associated with tumour progression. Methods: Related microarray data set of breast cancer was obtained from Gene Expression Omnibus database, and differential-expressed genes (DEGs) between two control samples and two treated samples were analysed using statistical software R. We collected 50 epigallocatechin-3-gallate(EGCG)-related genes and 119 breast cancer-related genes to create a knowledge base for following pathway analysis. Key findings: A total of 502 mRNAs were identified as DEGs based on microarray analysis. Upregulated DEGs mainly enriched in nuclear nucleosome, cell adhesion, DNA packaging complex, Wnt-activated receptor activity, etc ., while the downregulated DEGs significantly enriched in ncRNA processing, mitotic nuclear division, DNA helicase activity, etc . DEGs mostly enriched in gap junction, cell cycle, oxidative phosphorylation, focal adhesion, etc . EGCG suppressed FAK signalling pathway. Furthermore, EGCG could inhibit breast cancer cell proliferation and promote apoptosis by modulating CCND1. Conclusions: Epigallocatechin 3-gallate might exert influence on breast cancer progression through inhibiting focal adhesion kinase (FAK) signalling pathway.